2011
DOI: 10.1021/mp2000692
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Potential Anticancer Drugs Designed To Overcome Glutathione Transferase Mediated Resistance

Abstract: Resistance against anticancer drugs remains a serious obstacle in cancer treatment. Here we used novel strategies to target microsomal glutathione transferase 1 (MGST1) and glutathione transferase pi (GSTP) that are often overexpressed in tumors and confer resistance against a number of cytostatic drugs, including cisplatin and doxorubicin (DOX). By synthetically combining cisplatin with a GST inhibitor, ethacrynic acid, to form ethacraplatin, it was previously shown that cytosolic GST inhibition was improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 52 publications
6
67
1
Order By: Relevance
“…Catalytic rates were in general agreement with previous results for DNS–DOX (Figure 2B). 8 Oxidative activation of MGST1 or loss of activity of GSTP1 upon storage account for the differences observed. GSTA1, which was not yet tested with DNS–DOX, showed a very high turnover of 13780 ± 120 nmol/min/mg that by far exceeded the activity of MGST1 (463 ± 7 nmol/min/mg) and GSTP1 (18.7 ± 2 nmol/min/mg).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Catalytic rates were in general agreement with previous results for DNS–DOX (Figure 2B). 8 Oxidative activation of MGST1 or loss of activity of GSTP1 upon storage account for the differences observed. GSTA1, which was not yet tested with DNS–DOX, showed a very high turnover of 13780 ± 120 nmol/min/mg that by far exceeded the activity of MGST1 (463 ± 7 nmol/min/mg) and GSTP1 (18.7 ± 2 nmol/min/mg).…”
Section: Resultsmentioning
confidence: 97%
“…Our study showed that the prodrugs tested were more toxic to GST overexpressing cells compared to control cells, indicating that the GSTs tested could activate the prodrugs and release DOX. 8 …”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of GSTs in many kinds of tumors encourages studies with agents able to promote down regulation of these enzimes (Zhao et al, 2011), GST-actived pro-drugs aiming selective action (Pezzola et al, 2010; Johansson et al, 2011; Kogias et al, 2011) and GSTs inhibitors aiming overpass drug resistance (Cui et al, 2008; Tentori et al, 2011). However, nowadays, there is no GST-based approach consistent enough to be adopted as clinical adjuvant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One important consideration in the development of cancer treatment regimens is resistance against anticancer drugs, which remains a serious obstacle [5]. Indeed, microsomal glutathione transferase 1 (mGST1) and glutathione transferase π (GST π) are often overexpressed in tumors and confer resistance against a number of cytostatic drugs, such as cisplatin and doxorubicin (DOX) [6]. To address this point, the diuretic drug ethacrynic acid (EA, Edecrin) 1, an inhibitor of π class glutathione S-transferase, has been tested against multiple myeloma, and as adjuvant in clinical trials [7].…”
Section: Introductionmentioning
confidence: 99%